2015
DOI: 10.1523/jneurosci.3075-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Contrast Responses in the Extrastriate Cortex of Blindsight Patients

Abstract: When the human primary visual cortex (V1) is damaged, the dominant geniculo-striate pathway can no longer convey visual information to the occipital cortex. However, many patients with such damage retain some residual visual function that must rely on an alternative pathway directly to extrastriate occipital regions. This residual vision is most robust for moving stimuli, suggesting a role for motion area hMTϩ. However, residual vision also requires high-contrast stimuli, which is inconsistent with hMTϩ sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 64 publications
5
42
0
Order By: Relevance
“…Here, too, the progress of vision training in subacutes (versus chronics) points towards greater involvement of residual V1 circuits. Performance in subacute CB fields more closely resembles that in V1-intact controls both in terms of the faster timescale of perceptual learning on the CDDI task (57), and the ability to transfer learning/recovery to untrained tasks, including to motion contrast sensitivity (55,58). Additionally, CDDI training also improved fine direction discrimination in subacutes around a motion axis orthogonal to that trained (since the FDD task involved global motion discrimination along the vertical axis).…”
Section: Substrates Of Preserved Vision and Mechanisms Of Vision Restmentioning
confidence: 76%
See 1 more Smart Citation
“…Here, too, the progress of vision training in subacutes (versus chronics) points towards greater involvement of residual V1 circuits. Performance in subacute CB fields more closely resembles that in V1-intact controls both in terms of the faster timescale of perceptual learning on the CDDI task (57), and the ability to transfer learning/recovery to untrained tasks, including to motion contrast sensitivity (55,58). Additionally, CDDI training also improved fine direction discrimination in subacutes around a motion axis orthogonal to that trained (since the FDD task involved global motion discrimination along the vertical axis).…”
Section: Substrates Of Preserved Vision and Mechanisms Of Vision Restmentioning
confidence: 76%
“…The progressive silencing of these networks may be the result of trans-synaptic retrograde degeneration coupled with a sort of "visual disuse atrophy", whereby weak, surviving connections getting pruned and/or down-weighted over time, as patients learn to ignore the less salient visual information within corresponding regions of their blind fields. That this vision is mediated by V1 itself is supported by the relative preservation of contrast sensitivity within the perimetric blind field, with the CSFs more reflective of the contrast response of V1 (51)(52)(53) than MT, which saturates at low levels of contrast (54,55) and shifts to higher spatial frequencies as contrast increases (56). After stroke, without intervention, over a matter of months the substrates of this initially-preserved vision appear to be lost.…”
Section: Substrates Of Preserved Vision and Mechanisms Of Vision Restmentioning
confidence: 99%
“…Blindsight was determined according to performance on a high salience 2-AFC temporal detection paradigm presented within the blind region of the visual field ( Figure 1A ). Patients detected the interval in which the target appeared ( Figure 1B ) and were classified as ‘blindsight positive’ if average performance or performance for stimuli of 100% contrast was significantly above chance ( Figure 1C ; Ajina et al, 2015b ). Based on these criteria, 12 were classified as ‘blindsight positive’ and this relatively sensitive binary measure allowed us to be confident that patients labelled as ‘blindsight negative’ (n = 5) showed no residual visual function.…”
Section: Resultsmentioning
confidence: 99%
“…Since the geniculo‐striate pathway is not functional in patients with V1 damage, there must be an alternative route by which visual information can travel to the brain to facilitate blindsight . Recent work has provided evidence that a pathway between the lateral geniculate nucleus (LGN) and motion area hMT+ may underlie these abilities . Specifically, it has been shown that such a pathway is consistently present in patients who show blindsight, but not those without blindsight …”
Section: Introductionmentioning
confidence: 99%